A systematic review of sodium-glucose cotransporter 2 inhibitors and renal profiles among Japanese patients with type 2 diabetes mellitus - Junichi Mukai; Nakaba Okamura; Yuki Saito; Rie Kubota (BMC, 2023)
Abstract Background We conducted a systematic review and meta-analysis to summarize the available literature and comprehensively appraise the renal profiles of sodium-glucose cotransporter 2 inhibitors (SGLT2i) in Japanese patients with type 2 diabetes mellitus (T2DM). Methods The electronic databases MEDLINE, Ichushi-web, and ClinicalTrials.gov were searched for studies without language restrictions from their inception until 20 July 2023 and CENTRAL until 21 September 2021. Studies were included if they were double-masked randomized controlled trials (RCTs) (1) including Japanese patients with T2DM aged > 18 years who received SGLT2i or a placebo, (2) reporting at least one renal outcome of serum creatinine or the estimated glomerular filtration rate (eGFR), and (3) with a follow-up of > 12 weeks. Cross-over and open label trials were excluded. The risk of bias based on the Cochrane risk-of-bias tool for randomized trials (RoB 2) was appraised. We computed the weighed mean difference with 95%CI for each renal outcome and used a random-effects model (inverse variance method). Results We ultimately retrieved 13 RCTs including 2687 individuals in our review. The durations of RCTs ranged between 12 and 104 weeks. Only one trial had a longer duration of more than one year. Ten out of 13 RCTs reported serum creatinine, while nine included eGFR. Serum creatinine and eGFR were slightly worse with SGLT2i than with a placebo [mean difference 0.01 (95%CI 0.00 to 0.02) mg/dL, p = 0.002, mean difference − 1.30 (95%CI -2.23 to -0.37) mL/min/1.73 m2, p = 0.006, respectively]. Merged results revealed insignificant heterogeneity (I2 < 30%). Conclusion These results suggest that SGLT2i slightly worsens serum creatinine and eGFR in Japanese patients with T2DM. However, since the durations of most RCTs were short, the effects of eGFR in particular may be transient. Further evidence is needed from rigorous studies that focus on renal outcomes with a longer duration to confirm the present results.